2004
DOI: 10.1152/ajprenal.00211.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Cl/HCO3exchanger pendrin in the rat kidney is regulated in response to chronic alterations in chloride balance

Abstract: Pendrin (Pds; Slc26A4) is a new anion exchanger that is believed to mediate apical Cl(-)/HCO(3)(-) exchange in type B and non-A-non-B intercalated cells of the connecting tubule and cortical collecting duct. Recently, it has been proposed that this transporter may be involved in NaCl balance and blood pressure regulation in addition to its participation in the regulation of acid-base status. The purpose of our study was to determine the regulation of Pds protein abundance during chronic changes in chloride bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 43 publications
9
106
0
1
Order By: Relevance
“…Pendrin is upregulated by the injection of deoxycorticosterone pivalate, a pharmacologic analogue of aldosterone (16). However, we have demonstrated that pendrin also can be regulated in response to changes in Cl Ϫ intake by an aldosterone-independent mechanism (17). In vivo relevance of both mechanisms remains unsettled, but this question is of particular importance.…”
Section: CLmentioning
confidence: 89%
See 2 more Smart Citations
“…Pendrin is upregulated by the injection of deoxycorticosterone pivalate, a pharmacologic analogue of aldosterone (16). However, we have demonstrated that pendrin also can be regulated in response to changes in Cl Ϫ intake by an aldosterone-independent mechanism (17). In vivo relevance of both mechanisms remains unsettled, but this question is of particular importance.…”
Section: CLmentioning
confidence: 89%
“…Membrane fraction preparation and immunoblotting procedures for comparing two sets of samples of renal cortical membranes with regard to relative abundance of specific proteins were described in detail previously (17,24). Coomassie blue-stained polyacrylamide gels were used to control equality of protein loading for each series, as described in detail previously (17,24).…”
Section: Immunoblot Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased chloride delivery to the distal nephron and collecting duct is associated with reduced pendrin expression levels (139,192). Apparently, pendrin expression is sensitive to luminal chloride concentration but less to systemic chloride status.…”
Section: Ae1mentioning
confidence: 99%
“…A role of pendrin in collecting duct chloride reabsorption is further supported by the findings that pendrin expression is regulated during chloride depletion (197,208), Pds KO mice are resistant to DOCA and NaCl induced hypertension (196), and angiotensin II stimulates chloride reabsorption in isolated CCDs from wildtype but not from pendrin deficient mice (132) Pendrin activity may be controlled on at least four different levels, namely mRNA and protein expression as well as subcellular localization. Enhanced luminal pendrin localization was observed in animals loaded with bicarbonate (203), given DOCA (196), or during chloride depletion (197), whereas several treatments altered total pendrin abundance in the kidney (57,67,139,192,203). Studies in various cell lines provided evidence for direct regulatory domains in the promoter region sensitive to intracellular pH and possibly to aldosterone (1).…”
Section: Ae1mentioning
confidence: 99%